Seeing the trees: what urban middle school students notice about the street trees that surround them. Issue 2 (15th March 2021) - Wyner, Yael; Doherty, Jennifer H.
ABSTRACT: Even highly urban environments are settings for outdoor learning of local biodiversity, for they contain easily accessible street tree diversity that students walk pass daily. This study uses pre/post assessments and a tree observation curriculum grounded in scientific observation practice to understand the everyday and scientific tree observation practice of urban middle school students of mixed socioeconomic status (SES). Specifically, it examined students' abilities to name trees, the specific features of trees students noticed, and the botanical vocabulary they used to describe the trees they pass daily. Participants included 308 intervention students and 265 comparison students (11–14 years old) in six public New York City middle schools. Findings show that without the intervention students could not identify common street trees (oak, maple, honey locust), that they did not notice key tree features like leaf arrangement and shape and that they lacked the botanical vocabulary to accurately describe the features of the trees they see daily. Instead, students mostly differentiated trees by obvious uninformative gross features like overall tree size. Generalised multilevel statistical models of pre/post test results show that the ability to name, notice, and describe trees with botanical terminology improved with the study intervention. Students from medium SES schools had more prior knowledge and showed greater growth in learning than students from low SES schools.